The Effect of In Vitro Digestion on Matcha Tea (Camellia sinensis) Active Components and Antioxidant Activity - Koláčková, Tereza; Sumczynski, Daniela; Minařík, Antonín; Yalçin, Erkan; Orsavová, Jana (Antioxidants, 2022)
This study investigates the effects of in vitro digestion on the antioxidant activity and release of phenolics, xanthine alkaloids, and L-theanine contents of matcha. It establishes digestibility values between 61.2-65.8%. Considering native matcha, the rutin content (303-479 μg/g) reached higher values than catechin (10.2-23.1 μg/g). Chlorogenic acid (2090-2460 μg/g) was determined as predominant. Rutin, quercetin, ferulic, ellagic, and caffeic acid were the least-released phenolics, and their remaining residues reached 76-84%. Protocatechuic, hydroxybenzoic acid, epigallocatechin, and epigallocatechin-3-gallate were the best-released phenolics, with the remaining residues under 1%. Caffeine, L-theanine, and theobromine contents in native matcha reached 16.1, 9.85, and 0.27 mg/g, respectively. Only caffeine (3.66-5.26 mg/g) and L-theanine (0.09-0.15 mg/g) were monitored in the undigested residue, representing 13 and 0.1% of the remaining part, respectively. A chemiluminescence assay showed that water-soluble antioxidants showed significant antioxidant activity in native matcha, while lipid-soluble compounds showed higher antioxidant activity in the undigested samples. Cinnamic and neochlorogenic acids were determined as the main contributors to the ACW values in the undigested matcha, epicatechin, and quercetin in the ACL fraction. The application of the digestion process reduced the antioxidant activity by more than 94%. SEM has proved specific digestion patterns of in vitro digestibility of matcha.